Nationwide survey on the operational status of electron accelerators for radiation therapy in Japan - Yamaguchi, Ichiro; Tanaka, Shinji; Fujibuchi, Toshioh; Kida, Tetsuo; Nagaoka, Hiroaki; Watanabe, Hiroshi (Radiological physics and technology, 2010)
A nationwide survey was conducted on electron accelerators for radiation therapy in Japan for obtaining fundamental data on the actual operational situation of these accelerators. The research subjects were all medical institutions equipped with electron accelerators for radiation therapy (874 accelerators) in Japan. Postcards explaining the purpose and procedure of the survey were sent to each institution. Each institution was requested to download a questionnaire from the website and return it by e-mail. We obtained the following results. Energy: about 90% of the accelerators did not exceed 10 MeV as the permitted maximum energy. Beam intensity: a total of 94% of the accelerators did not exceed 4 Gy/min as the mean exposure dose rate. Beam time: a total of 74% of the accelerators were below half of the permitted maximum beam time. However, 2% of the accelerators exceeded 90% of the permitted maximum time. Cumulative dose: about 10% of institutions obtained permission not to use the maximum beam time, but to use the maximum cumulative dose to secure sufficient beam time. From these results, it became clear that the induced radioactivity based on the maximum beam current and the maximum operating time under an official permit would be overestimated. Therefore, the neutron dose should be assessed by use of a daily operational record, not from an official permit.